(untitled) (Global Journal of Science Frontier Research, 2025)
Photons are matter that have energy but are almost massless 4 . Photons oscillate because of their energy. Photons tend to share energy with other matter to form the minimum energy bonds. When bonded photons get extra energy than their bonding force, they become free photons. Free photons travel by oscillating because of the extra energy, in the direction of leaving the energy source, at the speed of almost 300,000 km per second 3 , until they transfer the extra energy and become bonded photons again. Thus, free photons are proposed to be the energy carriers of the Universe, and the actual substance of aether.